2D Layered Dipeptide Crystals for Piezoelectric Applications (Adv. Funct. Mater. 43/2021). (20th October 2021) - Zelenovskii, Pavel S.; Romanyuk, Konstantin; Liberato, Michelle S.; Brandão, Paula; Ferreira, Fabio F.; Kopyl, Svitlana; Mafra, Luís M.; Alves, Wendel A.; Kholkin, Andrei L.
Abstract : Organic Piezoelectrics In article number 2102524, Pavel S. Zelenovskii, Andrei L. Kholkin, and co‐workers use the co‐assembly of L, L‐ and D, D‐enantiomers of diphenylalanine dipeptide to achieve a new layered organic piezoelectric with high out‐of‐plane piezoelectric activity and a d33 coefficient 10 times higher than that of quartz. Weakly bonded layers can be exfoliated and used as 2D functional elements of biocompatible MEMS, energy harvesting and lab‐on‐chip devices, etc.